The art of the possible : Politics and governance in modern British history, 1885-1997: Essays in memory of Duncan Tanner - Tanner, Duncan; Edwards, Andrew, 1964-; Williams, Chris, 1963- (Book collections on Project MUSE., 2015)
This title explores some of the major transitions, opportunities and false dawns of modern British political history. It engages with the scholarly legacy of Professor Duncan Tanner (1958-2010) whose work was focused on the political process and on politics in government.